Work satisfaction of the self-employed: The roles of work autonomy, working hours, gender and sector of self-employment. (May 2016) - Sappleton, Natalie; Lourenço, Fernando
Studies on segregation in employment are suggestive of higher levels of job satisfaction in female-dominated occupational settings. This research investigates whether this effect is replicated in self-employment. We explore whether satisfaction differentials are related to differences in autonomy and working hours. Our hypotheses are tested using data from the European Social Survey. The final sample consists of 1079 males and 326 females. Our research suggests that differences in job satisfaction among self-employed men and women should not be attributed to gender but to gender composition of sector. Our study contributes to our understanding of gender within a sectoral perspective and the significance of work autonomy and level of working hours to improve work satisfaction of the self-employed.